Real options compared to traditional company valuation methods: Possibilities and constraints in their use - Ulyana Dzyuma (e-Finanse: Financial Internet Quarterly, 2012)
The subject of the article is the presentation of an unconventional method of establishing the value of the company together with investment ventures basing on the concept of real options (Real Option Valuation ROV). The option calculation can be applied in many areas, such as: evaluation of investment effectiveness, valuation of the company and its separate parts, estimating the value of company assets and liabilities, credit risk assessment. The concept of real options is very popular all over the world. However, in Poland we rarely use option methods in the above areas, although the method is currently considered a revolutionary solution to the problem of underassessment of huge risk projects.
Keywords: G12; G32; M21; 330; real options; company valuation methods; binomial model; Black-Scholes model